(untitled) (Academicia Globe: Inderscience Research, 2024)
This article examines the issues of improving the tax collection mechanism, improving service and education of taxpayers, simplifying the tax system and procedures, developing effective communication channels between taxpayers and tax authorities, improving tax collection mechanisms. In addition, the article examines theoretical and practical aspects of building trust and perception of fairness and applying effective enforcement measures, increasing compliance with legislation, trends in the development of relations, and the main causes of tax arrears on taxes and fees.